2015
DOI: 10.1128/jcm.03052-14
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Presepsin (sCD14-ST) for Prediction of Bacterial Infection in Cerebrospinal Fluid Samples from Children with Suspected Bacterial Meningitis or Ventriculitis

Abstract: P lacement of external ventricular drainage (EVD) and draining of the cerebrospinal fluid (CSF) when intracranial pressure (ICP) is elevated are frequently used for treating intracranial hypertension caused by a variety of neurological conditions. However, such an invasive procedure allows free entrance for bacteria and presents an increased risk of infection that can lead to meningitis, ventriculitis, or even death. The incidence of EVD-related ventriculitis ranges from 10% to 27% according to the literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 35 publications
2
25
0
1
Order By: Relevance
“…And there are reports showing its superiority to CRP in differentiating bacteremic SIRS from that of other causes [10]. Its diagnostic efficacy has been proved in various fields such as surgery, burn, neonates, and central nervous system [1114]. However, the reliability of presepsin in febrile neutropenia has not been well demonstrated so far.…”
Section: Discussionmentioning
confidence: 99%
“…And there are reports showing its superiority to CRP in differentiating bacteremic SIRS from that of other causes [10]. Its diagnostic efficacy has been proved in various fields such as surgery, burn, neonates, and central nervous system [1114]. However, the reliability of presepsin in febrile neutropenia has not been well demonstrated so far.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Stubljar et al 5 in their work, compared diagnostic accuracy of presepsin, to predict bacterial infection in comparison to established biomarkers like biochemical analysis of CSF and they found that presepsin was significantly higher in children with clinically proven ventriculitis compared to those without meningitis/ventriculitis and AUC for presepsin, leucocytes and proteins measured in CSF were 0.877, 0.798 and 0.857, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Presepsin can also be detected in the CSF ( 31 ) and may indicate microglial activation to bacterial infection within the CNS. A further attractive aspect of measuring CSF PSP is that, as a protein activated by bacterial infections, it should be insensitive to blood in the CSF and chemical meningitis, both common situations that complicate the diagnosis of NI-CNS in neurocritical care patients.…”
Section: Introductionmentioning
confidence: 99%
“…A further attractive aspect of measuring CSF PSP is that, as a protein activated by bacterial infections, it should be insensitive to blood in the CSF and chemical meningitis, both common situations that complicate the diagnosis of NI-CNS in neurocritical care patients. A handful of studies have examined PSP in the CSF of children and neonates with bacterial meningitis, with some promising results ( 31 , 32 ). Its usefulness in adult neurocritical care patients with NI-CNS has yet to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%